1989
DOI: 10.1002/chin.198931293
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Molecular Modeling of γ‐Lactam Analogues of β‐Lactam Antibacterial Agents: Synthesis and Biological Evaluation of Selected Penem and Carbapenem Analogues.

Abstract: From computational chemistry studies it is suggested that γ‐lactam analogues of penems and carbapenems possessing a 7β‐acylamino side‐chain present the pharmacophoric groups in close spatial similarity to the groups in biologically active cephalosporin and penicillin antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Recent efforts to [85], 5.2 [86], 5.3 [87], 5.4 [88], 5.5 [89], 5.6 [90], 5.7 [91] and 5.8 [92]). (B) Examples of inactive compounds (5.9 [93,94], 5.10 [93,94], 5.11 [88], 5.12 [95,96], 5.13 [97], 5.14 [98], 5.15 [99] and 5.16 [100]). …”
Section: Lactivicinmentioning
confidence: 99%
“…Recent efforts to [85], 5.2 [86], 5.3 [87], 5.4 [88], 5.5 [89], 5.6 [90], 5.7 [91] and 5.8 [92]). (B) Examples of inactive compounds (5.9 [93,94], 5.10 [93,94], 5.11 [88], 5.12 [95,96], 5.13 [97], 5.14 [98], 5.15 [99] and 5.16 [100]). …”
Section: Lactivicinmentioning
confidence: 99%
“…The /3-lactam ring, which is the hallmark of the well-studied penicillin and cephalosporin classes of antibiotics,3 is replaced by a pyrazolidinone ring4'5 (Figure 1). Recent computations and chemistry have shown that the fourmembered ring could be replaced by a 7-lactam ring,6 7 while retaining at last a very low level of antibacterial activity. Introducing a second nitrogen into the fivemembered ring significantly boosted activity to a useful range.8™12 The advantages of this ring bioisostere are that it opens up a novel structural series and it could in principle afford antibacterial or pharmacokinetic properties not achievable with traditional /3-lactam antibiotics.…”
mentioning
confidence: 99%